The Influence of Current Ratio, Leverage Ratio, and Return on Equity on Changes in Stock Prices: Study Library Research - Subagio, Mochammad (Dinasti Accounting Review, 2024)
Abstract: The purpose of this literature research is to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of financial management. The literature review research article on the influence of current ratio, leverage ratio and return on equity on changes in stock prices is a scientific literature article in the scope of financial management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous research, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Current ratio affects changes in stock prices; 2) Leverage ratio affects changes in stock prices; and 3) Return on equity affects changes in stock prices. Keywords: Stock Price Change, Current Ratio, Leverage Ratio, Return on Equity